PENGARUH KECERDASAN ADVERSITY QUOTIENT TERHADAP PRESTASI AKADEMIK (IPK) MAHASISWA PENDIDIKAN MATEMATIKA - Sidiq Aulia Rahman (UJMES (Uninus Journal of Mathematics Education and Science), 2017)
This study aims to examine the influence of Adversity Intelligence (AQ) on academic achievement (GPA) among Mathematics Education students at Islamic University of Nusantara. Samples for research Mathematics Education students of each generation and selected at random and proportionate. The data collected for this study were analyzed using regression analysis and the results showed that AQ only accounted for 0.62% (r = .062) changes in the variance of academic achievement. AQ still has the potential to be learned from other perspectives such as the success factors of Mathematics as a whole.